THE USE OF PROBLEM BASED LEARNING MODEL WITH IMPROVED LEARNING MEDIA FLASHCARD IN MATHEMATICS AT GRADE IV 01 TAMBAKSARI SDN ACADEMIC YEAR 2014/2015 - KURNIAWAN, IKO (KALAM CENDEKIA PGSD KEBUMEN, 2015)
Abstract: The use of Problem Based Learning Model with Improved Learning Media Flashcard in Mathematics at Grade IV 01 Tambaksari SDN Academic Year 2014/2015. The objectives of this research are to improve the learning of mathematics on the fourth grade student. The subjects were fourth grade students of SDN 01 Tambaksari, amounting to 25 students. This research was conducted in three cycles. Each cycle consisting of planning, action, observation, and reflection. The sources of data were from students, teachers, and observer. The techniques of data collection were observation, interview, and test. The validity of the data used the triangulation of sources and technique. The analysis of data consisting of data reduction, data description, and conclusion. The results of the research indicate that the use of PBL models with flashcard media can improve the learning of mathematics. Keywords: PBL, Flashcard, Mathematics Abstrak : Penggunaan Model Problem Based Learning dengan Media Flashcard dalam Peningkatan Pembelajaran Matematika pada Siswa Kelas IV SDN 01 Tambaksari Tahun Ajaran 2014/2015. Tujuan penelitian ini untuk meningkatkan pembelajaran matematika pada siswa kelas IV. Subjek penelitian adalah siswa kelas IV SDN 01 Tambaksari yang berjumlah 25 siswa. Penelitian ini dilaksanakan dalam tiga siklus. Setiap siklus terdiri dari perencanaan, pelaksanaan, observasi, dan refleksi. Sumber data penelitian adalah siswa, guru, dan observer. Teknik pengumpulan data dengan observasi, wawancara, dan tes. Validitas data menggunakan triangulasi sumber dan teknik. Analisis data meliputi reduksi data, penyajian data, dan penarikan kesimpulan. Hasil penelitian menunjukkan penggunaan model PBL dengan media flashcard dapat meningkatkan pembelajaran matematika. Kata Kunci: PBL, Flashcard, Matematika